The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12909-022-03393-9
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity formation of medical students: A mixed-methods study in a hierarchical and collectivist culture

Abstract: Background Professional identity formation (PIF) has been recognized as an integral part of professional development in medical education. PIF is dynamic: it occurs longitudinally and requires immersion in the socialization process. Consequently, in the medical education context, it is vital to foster a nurturing learning environment that facilitates PIF. Aim This study assesses PIF among medical students in various stages of study and explores the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Considering the evidence, this study revealed the need for an explicit professionalism curriculum in clinical learning ( 15 , 19 , 23 , 29 ). The literature explained that learning professionalism has not been explicit in medical education, making it harder to prioritise professionalism in teaching, learning and assessment ( 19 , 30 ).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Considering the evidence, this study revealed the need for an explicit professionalism curriculum in clinical learning ( 15 , 19 , 23 , 29 ). The literature explained that learning professionalism has not been explicit in medical education, making it harder to prioritise professionalism in teaching, learning and assessment ( 19 , 30 ).…”
Section: Discussionmentioning
confidence: 90%
“…Thus, offline sessions were limited in time and did not provide a variety of cases, making it even harder for students to interact with patients and learn professionalism ( 26 , 27 ). The lack of interactions with patients resulted in anxiety and a loss of confidence about student competence ( 15 , 19 ). This finding highlights the importance of direct patient interactions and the clinical learning environment in learning professionalism ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most scholars believe that the cultivation of professional identity does not only derive from organizational behavior and individual thoughts, but it is largely initially formed during the stages of education and learning. Therefore, efforts to enhance and cultivate professional identity should commence from educational institutions [33].…”
Section: Discussionmentioning
confidence: 99%
“…Professional identity formation has become the focus of a diverse range of fields, including medical education [ 26 ]. Among health care professionals, studies have shown that the development of a shared core value set can have substantial benefits, including improving the well-being and resilience of physicians [ 27 ].…”
Section: Discussionmentioning
confidence: 99%